Participation of alpha-1 and alpha-2 adrenoceptors of the lateral hypothalamic area in water intake, and renal sodium, potassium and urinary Volume excretion induced by central administration of angiotensin II - Saad, W. A.; Guarda, I. F. M. S.; Ferreira, A. C.; Camargo, L. A. D.; Neto, A. F. S.; Santos, T. A. F. B. dos (Elsevier B.V., 2000)
The circumventricular structures and the lateral hypothalamus (LH) have been shown to be important for the central action of angiotensin II (ANGII) on water and electrolyte regulation. Several anatomical findings have demonstrated neural connection between circumventricular structures and the LH, the present experiments were conducted to investigate the role of the alpha-adrenergic antagonists and agonistic injected into the LH on the water intake, sodium and potassium excretion elicited by injections of ANGII into the lateral ventricle (LV), the water intake was measured every 30 min over a period of 120 min. The sodium, potassium and urinary volume were measured over a period of 120 min in water-loaded rats. The injection of ANGII into the LV increased the water intake, which was reduced by previous injection of clonidine (an alpha-2-adrenergic agonist) into the LH. The injection of yohimbine (an alpha-2-adrenergic antagonist) and prazosin (an alpha-l-adrenergic antagonist) into the LH, which was done before injecting ANGII into the LV, also reduced the water intake induced by ANGII. The injection of ANGII into the LV reduced the sodium, potassium and urinary volume. Previous treatment with clonidine attenuated the action of ANGII in reducing the sodium, potassium and urinary volume, whereas previous treatment with yohimbine attenuated the effects of ANGII but with less intensity than that caused by clonidine. Previous treatment with prazosin increased the inhibitory effects of ANGII in those parameters. The injection of yohimbine and prazosin, which was done before the injection of clonidine, attenuated the effect of clonidine on the ANGII mechanism. The results of this study led us to postulate that when alpha-2-adrenergic receptors are blocked, the clonidine may act on the imidazoline receptors to produce its effects on the ANGII mechanism. We may also conclude that the LH is involved with circumventricular structures, which present excitatory and inhibitory mechanisms. Such mechanisms are responsible for regulating the renal excretion of sodium, potassium and water, (C) 2000 Elsevier B.V.
Keywords: alpha-adrenoceptors; ANG II; CNS; hydromineral balance